THE REPRESENTATION OF THE FLAG IN THE PERUVIAN NARRATIVE: FROM THE NATIONALIST DISCOURSE TO SUBALTERN'S TESTIMONY - Quichua Ayvar, Grober Omar (2022)
This article analyzes the representation of the national flag in two specific episodes of the Peruvian narrative in order to expose how it can be used as a means that, on the one hand, enervates national sentiment and, on the other, denounces the injustices against the Ande communities. In the first place, in the story “El hombre de la bandera”, by the writer Enrique López Albújar, the flag is manifested as the symbol that breeds a foundational nationalist discourse. It inspires in the inhabitants of the Andes an intimate identification with Peru and defense of the territory with their own lives, despite the unquestionable injustices they have suffered historically. Second, in the novel Redoble por Rancas, by Manuel Scorza, the flag highlights the contradictions and fissures in the ideological base that sustains the nation project. The national banner fosters solidarity between the inhabitants of Rancas and the army, on the contrary, it accentuates the socio-cultural fragmentation of the country and offers a discourse of minorities. To do this, the concept of «imagined community» coined by Benedict Anderson and the theoretical contributions of decolonial criticism, by Aníbal Quijano, and postcolonial criticism, by Homi Bhabha and Partha Chatterjee, will be used.